(untitled) (Journal of Comparative & International Higher Education, 2022)
The collapse of the Soviet Union has dramatically impacted the work of scholars across the post-Soviet space. As their higher education systems have been transforming from the Soviet model of higher education, they have had to adapt themselves to maintain their academic work and career. This doctoral project compares the lives of scholars in Cambodia and Kazakhstan who lived as students and scholars under the influence of Soviet imperialism. As guided by the framework of legacy-innovation tensions and theory of accumulative advantage, interviews with nine Cambodian and eight Kazakh scholars were conducted to shed light on how they strategically dealt with transformational challenges to create opportunities for their academic work and career. This study shows that their strategies for pursuing academic careers rely on their achievement during the Soviet time to grab opportunities. Meanwhile, these strategies were also influenced by local contexts.